Blocking access to websites as a measure of copyright protection - Urbavičiūtė, Monika; Petreikis, Laimonas (Vilnius University Open Series, 2020)
The research is mainly focused on blocking acces to websites as one of the main measure of copyright protection in the online space. The concept and content of this copyright measure have been disclosed. The effectiveness and efficiency of website blocking has been thoroughly analyzed. From the practical aspect, the mechanism of blocking acces to a website has been disclosed. Italian and French ways of copyright protection on the internet were compared with the Lithuanian model. The legal relationship between the court and the public administration entity as the role of these entities were also examined. The rullings of the Lithuanian Supreme Court and the case law of the European Court Of Justice have been systematically reviewed. The problem of implementing such a measue in the context of human rights was analyzed. The transfer of such a regulatory mechanism to other legal spheres and its implementation therein was discussed.